A feasibility study of a crowdsourcing project in promoting and enriching the local history collection and user engagement of Quezon City Public Library - Biglete, Nicole Marie L. (School of Library and Information Studies, University of the Philippines Diliman, 2019)
Crowdsourcing is a novel concept adapted by the public libraries like National Library of Singapore and Australia in their projects. In this study, the researcher sought to determine the feasibility of integrating crowdsourcing to Quezon City Public Library’s projects with the objective to strengthen the local history collection and increase user engagement. The heads of the Management Information System (MIS) section, Local history (LH) section, and Technical division were interviewed to plan the project and discuss its feasibility.